Identifikasi Komposisi Mineral Batuan Teralterasi Menggunakan Spektroskopi SEM-EDX dan FTIR Pada Daerah Manifestasi Panas Bumi di Desa Mototompiaan Kecamatan Modayg Kabupaten Bolaang Mongondow Timur - Chikita Hulungo; Donny Royke Wenas; Anneke Rondonuwu (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Mototompiaan village is one part of the area that has geothermal potential, there are 2 types of manifestations that exist in the area that is in the form of hot springs and mud pool. The purpose of this study to determine mineral composition of rocks which is in the area around geothermal manifestation of hot springs by SEM-EDX and FTIR. Based on the result of identification using SEM-EDX in sample 1 shows that there are composition of Aluminium (Al) 6.11%, Fe 11,10% and Silica (Si) 82.79%, while sample 2 contains Aluminium (Al) 6.53%, Fe 9,16%, Co 2,85% and Silica (Si) 87.13%. The test result by FTIR spectroscopy can be known the types of minerals contained in rock samples are Hermatite, Arganite, Quartz, and Palygorskite.